Thermal/luminescence characterization and degradation mechanism analysis on phosphor-converted white LED chip scale packages. (July 2017) - Fan, Jiajie; Yu, Chaohua; Qian, Cheng; Fan, Xuejun; Zhang, Guoqi
Abstract: According to the requirements on minimizing the package size, guaranteeing the performance uniformity and improving the manufacturing efficiency in LEDs, a Chip Scale Packaging (CSP) technology has been developed to produce white LED chips by impressing a thin phosphor film on LED blue chips. In this paper, we prepared two types of phosphor-converted white LED CSPs with high color rendering index (CRI > 80, CCT ~ 3000 K and 5000 K) by using two mixed multicolor phosphor materials. Then, a series of testing and simulations were conducted to characterize both short- and long-term performance of prepared samples. A thermal analysis through both IR thermometry and electrical measurements and thermal simulation were conducted first to evaluate chip-on-board heat dissipation performance. Next, the luminescence mechanism of multicolor phosphor mixtures was studied with the spectral power distribution (SPD) simulation and near-field optical measurement. Finally, the extracted features of SPDs and electrical current-output power (I-P) curves measured before and after a long-term high temperature accelerated aging test were applied to analyze the degradation mechanisms. The results of this study show that: 1) The thermal management for prepared CSP samples provides a safe usage condition for packaging materials at ambient temperature; 2) The Mie theory with Monte-Carlo ray-tracing simulation can be used to simulate the SPD of Pc-white LEDs with mixed multicolor phosphors; 3) The degradation mechanisms of Pc-white LEDs can be determined by analyzing the extracted features of SPDs collected after aging. Highlights: The CSP technology minimizes size, guarantees performance uniformity and improves manufacturing efficiency for LEDs; The SPD of LED CSP with multicolor phosphors can be predicted by the Monte-Carlo ray-tracing simulation with Mie theory; The degradation mechanisms of LED can be determined from the features of SPDs extracted by statistical model fitting.